PENGARUH KEMAMPUAN KEUANGAN DAERAH TERHADAP PERTUMBUHAN EKONOMI DI WILAYAH SUMATERA SELATAN PERIODE 2005-2014 - Juairiah, Juairiah (Universitas Muhammadiyah Palembang, 2017)
Purpose – The study aims to determine how the influence of financial capacity of region on economic growth in Southern Sumatran Region in period 2005 to 2014.Design/methodology - The analysis was performed by multiple regression analysis models by a Pooled Least Square method and the fixed effect estimation models. The data used is panel data of five provinces in Southern Sumatra.Findings – The analysis showed that the financial capacity in Southern Sumatra region is significantly affecting the economic growth.